Neutrophil-released enzymes can influence composition of circulating immune complexes in multiple sclerosis. (18th August 2018) - Paryzhak, S.; Dumych, T.; Mahorivska, I.; Boichuk, M.; Bila, G.; Peshkova, S.; Nehrych, T.; Bilyy, R.
Abstract: During NET formation, the content of neutrophils granules is released into the intercellular milieu. Consisting of many proteases and ROS species, formed NETs were shown to degrade cytokines (Schauer, Nat Med, 2014); while the content of neutrophil's azurophilic granules proved to contain glycosidases, secreted upon activation (Thaysen-Andersen, JBC, 2015), and formation of autoantibodies to neutrophil beta-glucoronidase was connected with the level of anti-MPO antibodies (Ab) (Martensson, Autoimmunity, 1992). Taking into account these facts, we aimed to investigate the possibility of NET-related changes in glycan composition on circulating IgG molecules and IgG–IgM immune complexes in multiple sclerosis (MS). This autoimmune disorder still has no reliable detection markers or established ways of treatment, besides widely accepted interferon therapy, making it a particularly interesting clinical condition. By applying capture lectin-ELISA, we analysed binding of α2, 6 sialyl-specific lectins SNA, PSqL, and core α1, 6-fucose specific lectin AAL to circulating IgG and related complexes in five groups of MS patients: untreated (17 persons); undergoing therapy with interferon (IFN) β-1 b (15 persons), corticosteroids (methylprednisolone) (12 persons) and anti-B-cell monoclonal Ab (12 persons: Ocrelizumab, 6 persons and alemtuzumab, 6 persons). A group of 23 healthy donors served as control. Significant increase in neutrophil elastase activity, observed in the group of patients under corticosteroid treatment was also accompanied by sialyl-specific PSqL and SNA lectin binding to captured IgG molecules. Subsequent analysis demonstrated that sialic acid residues were exposed on free IgG and on circulating IgG–IgM immune complexes. Increased lectin binding was not observed for anti-myelin basic protein (one of the major autoAb in MS) Ab compared to total serum Ab. IFN therapy was accompanied by low neutrophil elastase activity and low amount of circulating immune complexes. Incubation of in vitro generated NETs with human serum revealed the digestion of high-molecular weight immune complexes with subsequent exposure of hidden glycoepitops. Obtained data indicate the potential of neutrophil-derived proteases to modify (partially degrade) circulating immune complexes leading to exposure of internal glycoepitops.